(untitled) (Research, Society and Development, 2020)
Analyze the scientific production about risk factors for developing postpartum depression. This study is an integrative literature review, carried out in the period from August to September 2020, The search was carried out through the Virtual Health Library (VHL) platform, using the LILACS, MEDLINE and databases through the Google Scholar Portal, the following descriptors were used to collect bibliographic data: “Risk factors”; "Depression"; “Postpartum”, combined with the operator by clicking “AND”. The literature points out that the risk factors for developing postpartum depression are: age, low economic income, low schooling, conflicting marital relationship, psychiatric history, alcohol and drug use, domestic violence, previous abortions, lack of religion , complicated previous births, family conflicts and teenage pregnancy after the baby is born. It was evidenced in the study that several social, physical and emotional aspects that influence the triggering of postpartum depression, as well as the repercussions that this pathology can cause both in the mother’s life, in her mother-baby and conjugal relationship, causing a whole disorder in the family and psychosocial scope.